Comparative Study on Macro Causes of Working Poverty: Focusing on Two-parent Households in OECD Countries - Sang-Yong Sim (Luxembourg Income Study (LIS), 2016)
This study investigates the macro (structural and institutional) factors influencing working poverty by comparing among major OECD countries. A pooled time-series regression analysis with unbalanced panel design was performed on data collected from eligible two-parent households. The supply-side prescription of a mixed capitalist economy produced marginal poverty alleviation. As a result, working poverty has become a pronounced social problem in many developed capitalist countries in recent years. However, rash generalizations regarding poverty convergence are limited because the severity of the problem varies greatly across countries. International differences in working poverty stem from differences in countries' institutional contexts and the roles of actors. Among welfare institution variables, the children and family spending, and the social assistance spending were found to contribute to reductions in working poverty. Among variables reflecting political institutions, the proportional representation, the left seat, and the cumulative left cabinet were found to contribute to reductions in working poverty. Among the labor market variables, the unionization rate, the employment protection for regular workers were also found to contribute to reductions in working poverty. Among CME nations, socialist democratic countries that pursue the high road (i.e., high skills-high wages) were found to have a superior record of reducing working poverty.
Keywords: 330; Comparative Poverty Study; Political and labor market institutions; Welfare institutions; Socio-structural Factors; Unbalanced Panel Design; Pooled Time-series-crosssectional Regression Analysis; Working Poverty; Korea